Analysis of Criminal Liability In Cases of Sexual Violence Against Children on The Grounds of Consent - Yusron, Lizzyana; Setyorini, Erny Herlin (Media Hukum Indonesia (MHI), 2025)
Sexual violence against children is a serious crime that threatens the fundamental rights of children to grow and develop optimally. One of the critical issues in such cases is the claim of “consent” from the victim, which perpetrators often use to avoid criminal liability. However, legally, children are considered incapable of giving valid consent to sexual activities. This article aims to analyze the criminal liability of perpetrators of sexual violence against children when invoking the defense of consent, as well as to examine the legal framework protecting children from sexual exploitation. This research employs normative legal methods with a statutory and conceptual approach. Data sources include national regulations, international legal instruments, and academic literature. The analysis is conducted deductively to produce systematic legal arguments. The results of the study indicate that consent given by a child in the context of sexual activity is legally invalid due to cognitive and emotional immaturity. Regulations such as the Child Protection Act and the Law on the Crime of Sexual Violence (UU TPKS) affirm that sexual violence against children remains a criminal offense, regardless of claims of consent. Perpetrators may be subject to severe criminal sanctions, including chemical castration and the installation of electronic monitoring devices